Miniemulsion polymerization technology - Mittal, Vikas (Salem, MA : Scrivener, 2010)
'Miniemulsion Polymeriziation Technology comprises 10 papers by many of the world's experts on the subject. It summarizes the recent advances in miniemulsion polymerization technology including the advances on the selection of surfactants and co-surfactants, the expansion of miniemulsion technology in various polymers and co-polymer systems, and the use of miniemulsion polymerization for the synthesis of advanced polymer particle morphologies. There have been a large number of texts on emulsion and other forms of polymerization methods, but miniemulsion polymerization, though it provides unique routes for polymer particle synthesis, has been neglected.'--
Includes bibliographical references and index.
Keywords: Emulsion polymerization; Microencapsulation; Nanoparticles